2017
DOI: 10.1007/s40259-017-0229-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sclerostin in Postmenopausal Osteoporosis: Focus on Romosozumab and Blosozumab

Abstract: Most current treatments for osteoporosis inhibit bone resorption and reduce total fracture numbers by about one-quarter. The identification of the osteocytic protein sclerostin as a potent regulator of bone turnover and bone density has led to the development of a new therapeutic class-agents that inhibit sclerostin activity, resulting in increased bone formation and reduced bone resorption. Romosozumab and blosozumab are monoclonal antibodies that bind to sclerostin, reducing its inhibition of Wnt signaling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Excessive GC has been shown to stimulate sclerostin secretion from osteocytes. Neutralizing antibodies against sclerostin, such as romosozumab, can promote Wnt signaling and improve osteoblast function [172]. Elsewhere, it has been reported that miR-29a can suppress the side effects of excessive GCs on osteoblast differentiation in vitro and restore Wnt signaling by regulating β-catenin acetylation [173].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Excessive GC has been shown to stimulate sclerostin secretion from osteocytes. Neutralizing antibodies against sclerostin, such as romosozumab, can promote Wnt signaling and improve osteoblast function [172]. Elsewhere, it has been reported that miR-29a can suppress the side effects of excessive GCs on osteoblast differentiation in vitro and restore Wnt signaling by regulating β-catenin acetylation [173].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Demonstration of SOST expression by multiple cell types and identification of SOST as an evolutionarily conserved key player in bone modeling in fishes expands the relevance of sclerostin to modeling regulation for both paracrine and autocrine signaling. Currently, a wave of new sclerostin-targeting therapies are being explored in an effort to control sclerostin’s antianabolic properties in the treatment of osteoporosis and other skeletal disorders [4244]. Our findings suggest great potential for the massively speciose clade of fishes, with both osteocytic and anosteocytic members, as a powerful and relevant platform for research in bone physiology, as well as fracture healing and bone therapeutics.…”
Section: Discussionmentioning
confidence: 91%
“…Sclerostin is a soluble protein secreted from osteocytes that differentiated from osteoblasts, which prevents Wnt from binding to low-density lipoprotein receptor-related proteins-5/6 transmembrane receptors [60]. This blockade prevents osteoblast differentiation to inhibit bone formation [60,61]. In a recent study, higher circulating sclerostin levels were observed in patients with advanced liver cirrhosis than in healthy controls or patients with early liver cirrhosis [62].…”
Section: Pathogenesismentioning
confidence: 99%